Prevalence and molecular characterization of multi-drug and extreme drug resistant Escherichia coli in companion animals in Bangladesh - Md. Hafizur Rahman; Abu Bakkar Siddique; Md. Aseif Hossain Zihadi; S. M. Soheb Ahmed; Md. Sazzad Hossain Sumon; Shihab Ahmed (Scientific Reports)
Abstract The study aimed to investigate multi-drug resistant (MDR) Escherichia coli (E. coli) in companion animals in Bangladesh, with a focus on the resistance profiles of isolates from non-food-producing animals. In 2023, the studied samples were from cats, dogs, and environmental sources linked with companion animal hospitals in Dhaka city, Bangladesh. E. coli was isolated using standard techniques and its antimicrobial resistance (AMR) was assessed against 23 antibiotics following the CLSI protocols. Metallo-beta-lactamase genes (bla NDM-1 and bla NDM-5) and mobile genetic elements (class 1 integron) were detected by multiplex PCR. The overall prevalence of E. coli was 70%, 76% in cats, 65.71% in dogs, and 65.71% in the environmental samples. Cefuroxime exhibited the highest resistance at 25%, while imipenem and nitrofurantoin showed the highest sensitivity at 100%, followed by ceftazidime at 95%. MDR strains made up 38.10%, while 11.90% were extremely drug-resistant (XDR). Additionally, 29% of E. coli were extended-spectrum beta-lactamase (ESBL) producers. The prevalence and association among class 1 integron and the resistant genes including bla NDM-1 and bla NDM-5 were also notable. This highlights the complex AMR challenges in these settings, including the presence of class 1 integron—a key element involved in capturing and transferring antimicrobial resistance genes.